The Archive and the Digital Age: Field Notes from the Pedagogical Front - Makaryk, Irena R.; Hemingway, Ann (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
The digital environment in which the humanities are now firmly immersed has opened the door to innovative ways for students to interact with traditional formats such as archival and print material, and to develop a deep and personal understanding of topics and issues. Libraries, museums and archives are in the unique position of facilitating the creation of digital initiatives in the classroom by offering up their collections as “learning laboratories,” and by sharing their expertise in technology, information, and digital literacy as well as data management. Through active collaboration with course instructors, they can build bridges between their collections and the digital skills students need in order to embrace the new learning paradigm and to help lead them into the future. This paper outlines an archival-digital pilot launched in 2015 at the University of Ottawa, Canada. It situates the project in its historical context; details its early and subsequent iterations; and surveys the assumptions, challenges, surprises, and pleasures of introducing students to archival sources and to acquiring digital skills.